Religious Moderation with the Concept of Ummatan Wasathan: Tafsir Al-Qur'an surah al-Baqarah verse 143 through Ma'na Cum Maghza - Muhamad Slamet Yahya; Huzdaeni Rahmawati; Zulfatun Ni’mah (Al-Fikru: Jurnal Ilmiah, 2022)
In order for Indonesia to develop as a plural and diverse nation, religious tolerance is very important. The idea of ​​Ummatan wasathan in the Qur'an is comparable to the word moderation. This idea instills the importance of being a rational, open and fair person. Religious moderation is so important because national pluralism does not always bring positive things. There are many problems caused by differences in ethnicity, race, and even religion. This paper aims to analyze the concept of Ummatan Washatan in Surah Al-Baqarah verse 143 through ma'na cum magazha. This research is descriptive and qualitative in nature, using the interpretation approach of ma'na cum magazha in understanding the meaning in the content of the verse. The research findings reveal that ummatan wasathan, which means that people are given the freedom to make decisions by making full use of their intelligence. Research also reveals that differences are God's will and serve as a test, and that giving advice or preaching must be done in a fair, open, and non-violent way.